Postural Control in Lowlanders With COPD Traveling to 3100 m: Data From a Randomized Trial Evaluating the Effect of Preventive Dexamethasone Treatment - Muralt, Lara; Furian, Michael; Lichtblau, Mona; Aeschbacher, Sayaka S.; Clark, Ross A.; Estebesova, Bermet; Sheraliev, Ulan; Marazhapov, Nuriddin; Osmonov, Batyr; Bisang, Maya; Ulrich, Stefanie; Latshang, Tsogyal D.; et al. (Frontiers in Physiology, 2018)
Objective To evaluate the effects of acute exposure to high altitude and preventive dexamethasone treatment on postural control in patients with chronic obstructive pulmonary disease (COPD). Methods In this randomized, double-blind parallel-group trial, 104 lowlanders with COPD GOLD 1-2 age 20-75 y, living near Bishkek (760 m), were randomized to receive either dexamethasone (2x4 mg/d p.o.) or placebo on the day before ascent and during a 2-day sojourn at Tuja-Ashu high altitude clinic (3100 m), Kyrgyzstan. Postural control was assessed with a Wii Balance BoardTM at 760 m and one day after arrival at 3100 m. Patients were instructed to stand immobile on both legs with eyes open during five tests of 30 s each, while the center of pressure path length (PL) was measured. Results With ascent from 760 to 3100 m the PL increased in the placebo group from median (quartiles) 29.2 (25.8 ; 38.2) to 31.5 (27.3 ; 39.3) cm (P< 0.05); in the dexamethasone group the corresponding increase from 28.8 (22.8 ; 34.5) to 29.9 (25.2 ; 37.0) cm was not significant (P=0.10). The mean difference (95% CI) between dexamethasone and placebo groups in altitude-induced changes (treatment effect) was -0.3 (-3.2 to 2.5) cm, (P=0.41). Multivariable regression analysis confirmed a significant increase in PL with higher altitude (coefficient 1.6, 95% CI 0.2 to 3.1, P=0.031) but no effect of dexamethasone was shown (coefficient -0.2, 95% CI -4.0 to 3.6, P=0.925), even when controlled for several potential confounders. PL changes were related more to antero-posterior than lateral sway. 22 of 104 patients had an altitude-related increase in the antero-posterior sway velocity of >25%, what has been associated with an increased risk of falls in previous studies. Conclusions Lowlanders with COPD travelling from 760 to 3100 m revealed postural instability 24 h after arriving at high altitude, and this was not prevented by dexamethasone.